2012
DOI: 10.1097/pec.0b013e31827122a9
|View full text |Cite
|
Sign up to set email alerts
|

Use of High-Flow Nasal Cannula Support in the Emergency Department Reduces the Need for Intubation in Pediatric Acute Respiratory Insufficiency

Abstract: High-flow nasal cannula used early in the development of pediatric ARI is associated with a decreased the need for intubation and mechanical ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
134
2
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(157 citation statements)
references
References 9 publications
(6 reference statements)
6
134
2
15
Order By: Relevance
“…126 There is evidence that high-flow nasal cannula improves physiologic measures of respiratory effort and can generate continuous positive airway pressure in bronchiolitis. [127][128][129][130] Clinical evidence suggests it reduces work of breathing 131,132 and may decrease need for intubation, [133][134][135][136] although studies are generally retrospective and small. The therapy has been studied in the ED 136,137 and the general inpatient setting, 134,138 as well as the ICU.…”
Section: Action Statement Profile Kas 6bmentioning
confidence: 99%
See 1 more Smart Citation
“…126 There is evidence that high-flow nasal cannula improves physiologic measures of respiratory effort and can generate continuous positive airway pressure in bronchiolitis. [127][128][129][130] Clinical evidence suggests it reduces work of breathing 131,132 and may decrease need for intubation, [133][134][135][136] although studies are generally retrospective and small. The therapy has been studied in the ED 136,137 and the general inpatient setting, 134,138 as well as the ICU.…”
Section: Action Statement Profile Kas 6bmentioning
confidence: 99%
“…[127][128][129][130] Clinical evidence suggests it reduces work of breathing 131,132 and may decrease need for intubation, [133][134][135][136] although studies are generally retrospective and small. The therapy has been studied in the ED 136,137 and the general inpatient setting, 134,138 as well as the ICU. The largest and most rigorous retrospective study to date was from Australia, 138 which showed a decline in intubation rate in the subgroup of infants with bronchiolitis (n = 330) from 37% to 7% after the introduction of high-flow nasal cannula, while the national registry intubation rate remained at 28%.…”
Section: Action Statement Profile Kas 6bmentioning
confidence: 99%
“…In a large case series of pediatric emergency department subjects who needed subsequent ICU care, introduction of HFNC in the emergency department was associated with fewer intubations in the emergency department, although there was no control group in this study, so this may have been due to other factors. 17 …”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] A single-centre retrospective study of children with acute respiratory insufficiency (including asthma, pneumonia, bronchiolitis and croup) requiring PICU admission found introduction of HHHFNC therapy in the emergency department to be associated with a reduction in intubation rate from 16% to 8%. 24 There are some limited data relating to the potential use of HHHFNC therapy in paediatric cardiac patients. A recent single-centre, randomised trial compared HHHFNC therapy with low-flow oxygen therapy after extubation in postoperative cardiac patients under the age of 18 months.…”
Section: Role Of Hhhfnc Therapy In Respiratory Distress Due To Conditmentioning
confidence: 99%